Sosialisasi Bullying Di SMP Sabilal Muhtadin Banjarmasin - Marhaeni Fajar Kurniawati; Zakky Zamrudi; Muthia Farida; Sri Mariati Soraidah; Novia Septia Ningsih; Dedi Norwahyuliadi; Siti Aisyah; Norkhalifah Norkhalifah (Jurnal Kabar Masyarakat, 2024)
As a community service team from the Kalimantan Islamic University Muhammad Arsyad Al Banjari Banjarmasin, we feel very honored and committed to making a positive contribution to society and the educational environment. Therefore, we have carried out outreach activities about bullying among junior high school students with the belief that this effort will have a significant impact in creating a school environment that is safer, friendlier and supports children's development. In various stages of this activity, we, together with students and the school, felt the spirit of collaboration to bring about positive change. Involving an expert in this event is an important step, as it provides an in-depth perspective on the concept of bullying and effective solutions. Through discussions, we witnessed students who initially may have felt hesitant or lacking courage begin to open up and dare to talk about their experiences with bullying. This moment is an important first step in reducing stigmatism towards the problem of bullying and helps students feel more confident in reporting or dealing with similar problems in the future.